Correlation of annealing temperature, morphology, and electro-mechanical properties of electrospun piezoelectric nanofibers. (3rd October 2017) - Baniasadi, Mahmoud; Xu, Zhe; Cai, Jizhe; Daryadel, Soheil; Quevedo-Lopez, Manuel; Naraghi, Mohammad; Minary-Jolandan, Majid
Abstract: Piezoelectric polymeric nanofibers, such as P(VDF-TrFE), are promising nanostructures for sensing/actuation applications where flexibility of the component is required, for example soft robotics, conformal sensors, and energy harvesting devices. A challenge in polymeric piezoelectric materials is that their electromechanical coupling efficiency must be improved to approach that of bulk piezo ceramics. The electromechanical coupling factor is proportional to Y d 2 (where Y is the elastic modulus, and d is the piezoelectric constant); therefore, the investigation of inter-dependence of these properties as function of thermal annealing is important. Although effect of thermal annealing on thin film of PVDF has been studied, however, detailed investigations of correlation of annealing temperature, morphology, and electro-mechanical properties of electrospun piezoelectric nanofibers have not been reported, in particular at single nanofiber level. We report on the effect of various annealing temperatures on mechanical and piezoelectric properties at the single nanofiber level using nanoindentation and piezoresponse force microscopy (PFM). FTIR, XRD, and WAXD spectroscopies were also employed to quantitatively and qualitatively explain the enhancement of these properties. Graphical abstract: Highlights: Investigated correlation of annealing temperature and properties of piezoelectric nanofibers. Annealing above the Curie temperature results in enhancement of β-phase crystalline phase. Enhancement in β-phase was confirmed using AFM nanoindentation and piezoresponse force microscopy. Annealing above the Curie temperature significantly improved the piezo constant of the fibers. An increase of ∼90% in the piezo constant and ∼170% in the modulus were achieved by annealing at 130 °C.